2009
DOI: 10.1002/ptr.2900
|View full text |Cite
|
Sign up to set email alerts
|

Spearmint herbal tea has significant anti‐androgen effects in polycystic ovarian syndrome. a randomized controlled trial

Abstract: Hirsutism in polycystic ovarian syndrome (PCOS), consequent to elevated androgen levels leads to significant cosmetic and psychological problems. Recent research in Turkey has shown that spearmint tea has antiandrogenic properties in females with hirsutism. No research has yet been undertaken to assess whether a reduction in androgen levels brought about by spearmint tea, translates to a clinical improvement in the degree of hirsutism. This study was a two centre, 30 day randomized controlled trial. Forty two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 9 publications
(4 reference statements)
0
77
1
Order By: Relevance
“…In regard to spearmint tea, an RCT of 41 PCOS women showed that spearmint tea twice a day for 1 mo significantly decreased free and total testosterone levels, improved patients' subjective assessments of their hirsutism, and increased LH and FSH compared with a placebo herbal tea (33). Further studies are needed to confirm these findings and further elucidate the mechanisms underlying the antiandrogenic effects of spearmint tea.…”
Section: Dietary Supplementsmentioning
confidence: 89%
See 1 more Smart Citation
“…In regard to spearmint tea, an RCT of 41 PCOS women showed that spearmint tea twice a day for 1 mo significantly decreased free and total testosterone levels, improved patients' subjective assessments of their hirsutism, and increased LH and FSH compared with a placebo herbal tea (33). Further studies are needed to confirm these findings and further elucidate the mechanisms underlying the antiandrogenic effects of spearmint tea.…”
Section: Dietary Supplementsmentioning
confidence: 89%
“…In addition, herbal tea reduces body weight and induced ovulation in androgen-sterilized rats (103). However, there are only two RCTs of herbal tea in PCOS, one using green tea (10) and the other spearmint tea (33).…”
Section: Dietary Supplementsmentioning
confidence: 99%
“…Cinnamon extract has been shown to reduce insulin resistance in in vitro and in vivo studies by increasing phosphatidyl inositol 3-kinase activity in the insulin signalling pathway and thus potentiating insulin action 12 .…”
Section: Twak -Cinnamomum Zeylanicummentioning
confidence: 99%
“…Research into the herb Mentha spicata was guided by traditional use for M a n u s c r i p t 23 hirsutism in Turkey (Grant, 2012). A randomised controlled trial by Grant in 2010 indicated that this herb had potential to be a beneficial treatment. In the questionnaire, its use was documented by one practitioner however; a tincture was used rather than an infusion as used in the trial.…”
Section: )mentioning
confidence: 99%